Assessment of Allometry in Environmental DNA and RNA Production From Ayu (Plecoglossus altivelis) in an Experimental Condition Using Mitochondrial and Nuclear Gene Markers - Toshiaki S. Jo; Yusuke Ozaki; Nao Matsuda; Hiroki Yamanaka (Environmental DNA)
ABSTRACT Recent studies demonstrated that integrating allometric scaling could strengthen the relationship between environmental DNA (eDNA) concentration and organism abundance. The finding has been supported mainly by field surveys but has not been verified sufficiently at the individual level in a controlled experimental condition. In addition, it remains unknown whether not only eDNA but also environmental RNA (eRNA) production scales allometrically with body mass. To address the knowledge gaps, we conducted a long‐term rearing experiment using ayu (Plecoglossus altivelis) to monitor the production of their eDNA and messenger and ribosomal eRNA in their growth from larvae to adults. Water samples were collected from the experimental tanks and P. altivelis eDNA and eRNA (eNAs) concentrations in water samples were estimated using a quantitative real‐time PCR with the mitochondrial and nuclear gene markers. In parallel with each water sampling, the number of fish individuals and total biomass in the tank were recorded. Regardless of gene and RNA types, individual‐level P. altivelis eNA concentrations were related to their allometric scaled mass (ASM), with the scaling coefficient (b) = 0.75, more strongly than their mean body mass. The result indicated that a larger individual produces lesser mass‐specific eNA particles, supporting the relevance of the allometric scaling in eDNA production at the population level observed in field surveys. Moreover, the ratios of some eNA concentrations significantly decreased with larger mean fish body mass in the tank. The finding may relate to the changes in intracellular physiology with individual growth and/or aging, having the potential to indicate the population's average body size. Our study offered insights into the production of various eNA particles depending on body size and metabolic rate and implications for a better understanding of the population's ecology and more effective stock management.